Un Louvre pour les artistes vivants ? Modalités d’appropriation du musée par et pour les artistes du xixe siècle - Claire Dupin de Beyssat (Les Cahiers de l'École du Louvre)
Since its founding, in 1793, the Musée du Louvre accorded an important place to the art of the period: artists lived there until 1848, worked there as copyists during the entire nineteenth century and presented their work regularly in the rooms of the museum. Despite their gradual exclusion from the picture rails of the Louvre, living artists – an expression that was omnipresent during this period – would, throughout the nineteenth century, appropriate the Louvre: its space, its museographical organisation and its ambitions. By studying three distinct phenomena, which more or less follow the career of a nineteenth-century artist, it clearly appears that the Louvre, even when it did not really contain works of its period, remains a model systematically cited by institutions for art education, diffusion and legitimation.